A direct communication proposal to test the Zoo Hypothesis. (November 2016) - de Magalhães, João Pedro
Abstract: Whether we are alone in the universe is one of the greatest mysteries facing humankind. Given the >100 billion stars in our galaxy, many have argued that it is statistically unlikely that life, including intelligent life, has not emerged anywhere else. The lack of any sign of extraterrestrial intelligence, even though on a cosmic timescale extraterrestrial civilizations would have enough time to cross the galaxy, is known as Fermi's Paradox. One possible explanation for Fermi's Paradox is the Zoo Hypothesis which states that one or more extraterrestrial civilizations know of our existence and can reach us, but have chosen not to disturb us or even make their existence known to us. I propose here a proactive test of the Zoo Hypothesis. Specifically, I propose to send a message using television and radio channels to any extraterrestrial civilization(s) that might be listening and inviting them to respond. Even though I accept this is unlikely to be successful in the sense of resulting in a response from extraterrestrial intelligences, the possibility that extraterrestrial civilizations are monitoring us cannot be dismissed and my proposal is consistent with current scientific knowledge. Besides, issuing an invitation is technically feasible, cheap and safe, and few would deny the profound importance of establishing contact with one or more extraterrestrial intelligences. A website has been set up (http://active-seti.info ) to encourage discussion of this proposal and for drafting the invitation message.